Factors associated with the mortality of patients with enterobacteriaceae carbapenem-resistant - Souza, Sara C. S.; Silva, Danilo F. da; Belei, Renata A.; Carrilho, Cláudia M. D. de M. (Medicina (Ribeirao Preto), 2016)
record of 591 patients that presented positive culture for CRE admitted from January 2012 to July 2013. Other factors associated with mortality of patients with CRE were: sex, age, microorganism isolation site, unit and length of stay, and clinical feature (infection and colonization). Data normality was tested by Shapiro-Wilk. Quantitative data was presented as median (interquartile range). The associations were made through 2x2 and tendency Chi-square test. Significance level was set at P<0.05. The increase of age was associated with a high frequency of not survivors. The isolation site: lower respiratory tract and blood were more frequent in not survivor’s patients. ICU inpatients also were associated with CRE not survivors, as well as longer length of stay and the clinical feature of infection. On the other hand, sex was not a factor associated with the mortality of patients. In conclusion, the present study noted an association between age, microorganism isolation site, patient unit, length of stay and clinical feature with the mortality of CRE patients. It is suggested that future studies investigate the rate of prevalence changes of cases of colonization or infection for CRE in university hospitals and establish prevention and control strategies